“WEALTH OR LOVE, WHAT DOES A WOMAN WANT?” AN IRONIC LOOK AT THE MIDDLE CLASS NORMS IN CHARLOTTE BRONTE’S JANE EYRE - Afina Murtiningrum (Universitas Islam Sultan Agung, 2017)
Jane Eyre is a novel written in the early nineteenth century (1847). It depicts the English society of the upper, middle and lower class and their habits and attitudes towards life. The opening of the novel points to social class, wealth and marriage as its major theme. Throughout the novel, the relationship between social awareness of class and marriage, especially dealing with money or property are highlighted, the reason why society tends to consider about social class, money and property in finding a suitable partner to marry. This paper relies on the examples from the novel to show how nineteenth-century women imagined their marriage. In terms of women’s social rights and roles, Charlotte Bronte tries to open readers' eyes to the idea that women's abilities should not be limited only to the sphere of the family. Bronte’s novel does not only attack Victorian class structure but also the issue of gender. Keywords : marriage, wealth, property, women’s roles, gender